Chasing Phantoms in the Archives: The Australia House Photographic Collection - Sassoon, Joanna (Archivaria, 2000)
The author’s discovery that an Australian government agency’s large historical photograph collection no longer exists intrigues her. She pursues an investigation into when, how, and why these records disappeared, and the most likely cause of their disappearance is traced. The article suggests that sensitivity to visual literacy in the agency’s current records management policies would ensure that further destruction of large photograph collections will not recur. RÉSUMÉ L’auteure fait un jour la découverte qu’une importante collection de photographies historiques d’Australie a disparue, ce qui l’intrigue. Elle mène alors une enquête sur le pourquoi, le quand et le comment de cette disparition et sur ses causes les plus probables. Cet article suggère qu’une plus grande sensibilité à la culture visuelle dans la politique de gestion des documents de l’agence permettrait qu’unepareille destruction de collections photographiques soit évitée à l’avenir.